Identification and Analysis of Underdeveloped Village in The Border Area of Bogor District (Studi Wirajaya Village Jasinga) - Herman; Hartini, Sri; Mulyaningsih, May (Journal of Social Transformation and Regional Development, 2022)
One measure of the success of village development is measured by the achievement of the Village Development Index (IDM), the status of success in the IDM is seen from 5 categories, namely (1). The status of villages is very disadvantaged, (2), underdeveloped villages (3), developing villages (4), advanced villages and (5), independent villages. The villages in the border areas are really cause for concern. Based on the size of the Village Development Index (IDM) 2020, the number of villages on the border that have underdeveloped status and are very disadvantaged is very dominant. Wirajaya village is the only village in Jasinga District that is included in the category of underdeveloped villages with an IDM in 2020 of 0.5819. Sampling was done by collecting data on all economic, social and environmental aspects. Each indicator has a score. The score was determined using the Analitycal Hierarchy Process (AHP) method. The calculation of the index on each dimension is carried out using the scoring method which is then transformed into an index. The social resilience index consists of 4 indicators: health, education, social capital, and housing. Health indicators have the lowest contribution of 0.57. The economic resilience index consists of 6 indicators, namely, indicators of diversity in production, trade, distribution access, access to credit, economic institutions, regional openness. Of the six indicators, the lowest contribution is the logistic distribution access indicator, which is 0.00. The environmental resilience index consists of 3 indicators, namely, environmental quality indicators, disaster-prone potential and disaster response. Of the three indicators, the lowest contribution is the disaster-prone potential indicator of 0.00.